Romanzo Criminale : la série dans un récit transmédial - Marta Boni (Mise au Point)
This paper analyzes the Italian TV series Romanzo Criminale through the concept of quality soap, trying to describe a new cultural and social phenomenon that is transmedia storytelling. This study has been developed combining an analysis of the show’s narratological structure with an experimental ethnographic study of its reception, with an emphasis on online spaces dedicated to discussion and parodic practices, in the context of the "participatory culture".